Aspectos jurídicos da comissão de meio ambiente e desenvolvimento sustentável da Câmara dos Deputados da República Federativa do Brasil de 2004 a 2016 - Silva, Sidney da Cunha Vida (2017)
The environmental issue tends to be somewhat prone to degradation, since the man uses its natural resources, in the midst of your financial/economic growth. In this way, is something worrying about your exploration, since, the constitutional text punctuation in your device art. 225 ""everyone is entitled to an ecologically balanced environment, common use of people and essential to healthy quality of life, and to the Government and the collective duty to defend it and preserve it for present and future generations"". However, in addition to the society, the Government also has the power to defend it and preserves it, in this way, the Legislature has emerged the need for creation of Committee to discuss and approve measures related to the protection of the environment, signaling a willingness not only to how to debate, discuss and create opinion on civil society, as well as the primordial function of proposing vote and boost laws justifying your nomenclature, namely to reconcile protection of the environment with the promotion of sustainable development in Brazil, in order to influence legislation and be a crucial Forum in formulating national policies that relate to the environment.